2017
DOI: 10.11591/ijpeds.v8.i3.pp1274-1284
|View full text |Cite
|
Sign up to set email alerts
|

The Coordinated Control of FACTS and HVDC Using H-infinity Robust Method to Stabilize the Inter-regional Oscillations in Power Systems

Abstract: This paper presents a new resistant control method for synchronized connection of FACTS & HVDC aiming to get the stability of small signal of the power system. The efficiency of the proposed controller on the stability of the entire tested system has been proved and also guarantees the stability against uncertainty and turmoil. Applying this method can also reduce the difficulties of oscillations between adjacent areas to generator without strengthening transmission lines or costly constraints on system perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Besides, an increase in active and reactive power between the buses and lines, and at the same time, voltage stabilization in the Main and Lake Buses in this SVC-HVDC model were obtained. However, this paper examined a comprehensive model for the simultaneous effects of all the two types of devices for power flow and controlled the active and reactive power simultaneously, which had not been done in any of the previous studies [9], [23]- [25], [29]- [31], [33], [34], [40], [52], [54], [57], [68]- [70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, an increase in active and reactive power between the buses and lines, and at the same time, voltage stabilization in the Main and Lake Buses in this SVC-HVDC model were obtained. However, this paper examined a comprehensive model for the simultaneous effects of all the two types of devices for power flow and controlled the active and reactive power simultaneously, which had not been done in any of the previous studies [9], [23]- [25], [29]- [31], [33], [34], [40], [52], [54], [57], [68]- [70].…”
Section: Resultsmentioning
confidence: 99%
“…SVC has been used to optimize the Newton-Raphson power flow modeling [29], [30]. In [31], a control method for the coordination of HVDC and FACTS was proposed with the aim of obtaining small signal stability of the power system, which indicated that by changing the parameters, the oscillation between adjacent areas for production was reduced. In [32], a multiple optimal power flow (OPF) solution method was presented with the presence of FACTS devices, which were very powerful and fine-tuned the unequal constraints of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], the ability to improve the voltage stability of two FACTS devices such as SVC and static synchronous compensator(STATCOM) has been compared. In [17] and [18], using two static synchronous series compensator (SSSC) and current source converter (CSC) devices, he improved the static stability of the voltage in the network. This reference has provided a mathematical model of the voltage dependence of SSSC and CSC devices.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is highly helpful when working with MIMO models, which can simultaneously satisfy a number of control objectives. However, it has certain downsides, including the requirement for adequate mathematical proficiency and the likelihood that it is unfeasible for large-scale systems [22], [23].…”
Section: Introductionmentioning
confidence: 99%